DECONSTRUCTING THE ‘SELF’ AND EMPOWERING THE ‘OTHER’: Visionaries in Colonial South India - Abraham, Molly (Journal of Dharma, 2018)
While contesting the normative, and existential postulates, which insinuates that self as a process of separating oneself out from the matrices of others, this study examines the relationality and interdependence of ‘self’ and the ‘other’, exploring the complexity and dynamics of missionary ‘self’ and the Indian ‘other’. While tracing the intricacies of the discourse of self through the prism of theoretical and empirical analysis, the study enumerates how missionaries ventured to empower the other by transcending the boundaries of nationality, language, culture and by deconstructing their ‘selves’. This paper presents the trajectory of social construction of the missionary ‘self’ as a fluid, dynamic and ongoing process whereas the Indian ‘others’ was negotiated itself in a dialectical relationship with the sociocultural context of their culture of origin and the host culture. It suggests that missionaries, well engaged with communities of different cultural landscapes, by teaching the socially and economically disadvantageous sections, deconstructed the conventional images of their ‘selves’ as strangers, firangis, foreigners, sojourners and resident aliens. By articulating the marginality and the profoundly ingrained ‘otherness’ of the underprivileged, they used transformative education as the most potential apparatus to create an inclusive society, which, they perceived, would instil a sense of transnational pastiche and intercultural interactions among the posterity.